2008
DOI: 10.1103/physrevd.77.045011
|View full text |Cite
|
Sign up to set email alerts
|

Black hole collapse simulated by vacuum fluctuations with a moving semitransparent mirror

Abstract: Creation of scalar massless particles in two-dimensional Minkowski space-time-as predicted by the dynamical Casimir effect-is studied for the case of a semitransparent mirror initially at rest, then accelerating for some finite time, along a trajectory that simulates a black hole collapse (defined by Walker, and Carlitz and Willey), and finally moving with constant velocity. When the reflection and transmission coefficients are those in the model proposed by Barton, Calogeracos, and Nicolaevici [r(w) = −iα/(ω … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…The DCE with partially reflecting mirrors in the one-dimensional models was considered in [53,102,117,131,132,[153][154][155][156][157][158][159]. The comparison of the Dirichlet and Neumann boundary conditions in terms of the solutions to Moore's Equation (6) was performed in paper [72].…”
Section: Partially Transparent Mirrors and General Boundary Conditionmentioning
confidence: 99%
“…The DCE with partially reflecting mirrors in the one-dimensional models was considered in [53,102,117,131,132,[153][154][155][156][157][158][159]. The comparison of the Dirichlet and Neumann boundary conditions in terms of the solutions to Moore's Equation (6) was performed in paper [72].…”
Section: Partially Transparent Mirrors and General Boundary Conditionmentioning
confidence: 99%
“…Notably, Moore [41], DeWitt [42], and later on, Davies and Fulling [38,39] initiated a program using field theories with external conditions, which eventually demonstrated that quantities like the expectation values of the stress-energy tensor, and the localization of particles using wave packets, can be calculated in various physical problems and used to extract significant physical consequences of the quantum fields. Indeed, there has been renewed interest [23,24,[43][44][45][46][47][48][49][50][51][52][53][54] in the moving mirror model in recent years due, in part, to claims of experimental verification of the dynamical Casimir effect [55,56]. In many of these particle production scenarios, various systems that exploit the simple mathematical set up of the (1+1)-dimensional moving mirror model have led to novel experimental designs.…”
Section: Introduction: Some Puzzles With Moving Mirrors and Evaporatimentioning
confidence: 99%
“…There are some examples of different reflecting conditions in Refs. [14,15], but these cannot be directly applied here. One can come up with an equation by noting that when we reverse the boundary condition, we must get a solution of the normal wave equation.…”
Section: -8mentioning
confidence: 96%
“…Here W is a pure phase and not relevant in the following, and F = ^aoutA l Baxut + a( 1 ,ut((A 1)T -l ) a xut (15) will not contribute to the transition element after normal ordering. With the above it is and thus…”
Section: Nomenclaturementioning
confidence: 98%